Subretinal Therapy: Technological Solutions to Surgical and Immunological Challenges - Ladha, Reza; Caspers, Laure E.; Willermain, François; de Smet, Marc D. (Frontiers in Medicine, 2022)
Recent advances in ocular gene and cellular therapy rely on precisely controlled subretinal delivery. Due to its inherent limitations, manual delivery can lead to iatrogenic damage to the retina, the retinal pigment epithelium, favor reflux into the vitreous cavity. In addition, it suffers from lack of standardization, variability in delivery and the need to maintain proficiency. With or without surgical damage, an eye challenged with an exogenous viral vector or transplanted cells will illicit an immune response. Understanding how such a response manifests itself and to what extent immune privilege protects the eye from a reaction can help in anticipating short- and long-term consequences. Avoidance of spillover from areas of immune privilege to areas which either lack or have less protection should be part of any mitigation strategy. In that regard, robotic technology can provide reproducible, standardized delivery which is not dependent on speed of injection. The advantages of microprecision medical robotic technology for precise targeted deliveries are discussed.